Association between splenic volume changes and prognosis in advanced gastric cancer patients receiving chemotherapy combined with immunotherapy - Li, Zhiying; Liu, Weiwei; Zhang, Guilin; Fu, Xiaona; Li, Yi; Lou, Jie; Gong, Bingxin; Li, Lingli; Yang, Lian; Zhang, Peng (Frontiers in Oncology, 2026)
Background and aimThe prognostic value of splenic volume (SV) in patients with advanced gastric cancer receiving chemotherapy combined with immunotherapy remains unclear. This study aimed to evaluate the association between CT-assessed changes in SV and clinical outcomes, exploring its potential as a prognostic biomarker.MethodsThis retrospective cohort study included 138 advanced gastric cancer patients receiving chemotherapy combined with immunotherapy. Patients were stratified into an increased group (ΔSV > 14%, n = 87) and a non-increased group (ΔSV ≤ 14%, n = 51) based on the optimal cutoff value of 14% for the annualized change in splenic volume (ΔSV). Kaplan-Meier survival analysis, Cox proportional hazards models, and restricted cubic spline analyses were used to assess prognostic associations. A nomogram incorporating ΔSV was constructed for survival prediction.ResultsThe increased group showed significantly shorter median progression-free survival (PFS) (14.8 vs. 26.6 months, P < 0.001) and overall survival (OS) (18.9 vs. 30.9 months, P < 0.001) compared to the non-increased group. Multivariate analysis identified ΔSV >14% as an independent risk factor for both PFS (HR, 0.424 [95% CI, 0.238 - 0.755]; P< 0.001) and OS (HR, 0.233 [95% CI, 0.109 - 0.501]; P < 0.001). A nomogram integrating ΔSV, stages, and other indicators demonstrated significantly better predictive performance than a stages-only model (1-year OS AUC: 0.802 vs. 0.564; 2-year OS AUC: 0.883 vs. 0.686).ConclusionsIncreased SV is associated with poorer clinical outcomes in advanced gastric cancer patients receiving chemotherapy combined with immunotherapy.